Overview of middle and east-european market’s mergers and acquisitions in 2012 to 2017 period - Gira, Dominik (Współczesne Problemy Zarządzania, 2019)
As the markets of Middle and East-European countries, after transformation emerge more and more, mergers and acquisitions are becoming increasingly common form of business restructuring and strategic alliance. Increasing frequency of this type of deals pose as a pressure on business people and government officials at all levels to have a basic understanding of reasoning behind such actions and their mechanics. The following article provides a review of relevant sources containing theories of mergers and acquisitions. Its aim is to present highlights of merger and acquisition activity in context of these aforementioned theories on data concerning Middle and East-European countries, in a defined time-frame starting form 2012 to 2017.